Opioid substitution therapy or hidden opioids are a minefield for nalmefene: an atypical case series of 11 patients in Lorraine. (9th May 2017) - Yéléhé‐Okouma, Melissa; Martini, Hervé; Lemarié, Jérémie; Labroca, Pierre; Petitpain, Nadine; Gibaja, Valérie; Paille, François; Gillet, Pierre
Abstract: Opioid antagonists such as naltrexone and nalmefene are used in drug therapy for alcoholism. Nalmefene, approved in Europe in February 2013 for the reduction of alcohol consumption, is used in patients with alcohol dependence. We report 11 cases of opioid withdrawal syndrome after a single dose of nalmefene in patients usually treated with methadone, buprenorphine, but also with fentanyl or loperamide. Nalmefene is both a partial agonist and an antagonist of opioid receptors. Regarding to its opioid antagonist activity, nalmefene is contraindicated in patients with an opioid treatment. Therefore, when prescribing or delivering nalmefene, healthcare professionals need to be vigilant about any type of opioid exposure, even masked or hidden, to avoid these potential life‐threatening syndromes.